Meningkatkan Kinerja Pengelolaan Pinjaman Luar Negeri Pasca Covid 19 - Widjanarko Widjanarko (Pusat Pembinaan Jabatan Fungsional Bidang Pengembangan Kompetensi Pegawai ASN, 2021)
This study discusses the Government's considerations in maintaining foreign loans as a complement to State Securities (SBN) to finance the deficit in the State Revenue and Expenditure Budget (APBN). There are three considerations to maintain the foreign loan procurement policy in financing the APBN deficit. First, the cost is relatively cheap. Second, the benefits in supporting the transfer of technology. Third, investment lever (/multiplier effect). This study concludes that the procurement of foreign loans has not fulfilled one of the considerations, namely cheap financing. The slow implementation of projects in the field resulted in most of the slow disbursements being extended. As a result, the Government must increase the cost of the commitment. The classic problem of delays in foreign loan projects has been around for a long time and is expected to continue. The delay was contributed by factors in the planning stage; effectiveness of loans, budgeting, auctions, disbursement, and implementation in the field. The non-implementation of the three line of defense model is one of the contributors to the failure of risk mitigation of foreign loan projects. There is a perception that increasing debt to combat the Covid-19 pandemic is normal. The momentum of the Covid-19 pandemic has become a challenge to change the old paradigm. That the cost of foreign loans, is relatively expensive, especially if it is late.